Spasticity treatment with onabotulinumtoxin A: data from a prospective German real-life patient registry - Schramm, Axel; Ndayisaba, Jean-Pierre; Brinke, Matthias Auf Dem; Hecht, Martin; Herrmann, Christoph; Huber, Martin; Lobsien, Elmar; Mehnert, Sabine; Reuter, Iris; Stenner, Andrea; Van Der Ven, Christian; Winterholler, Martin; et al. (Journal of Neural Transmission, 2014)
This study aimed at providing real-life baseline, injection and outcome data for the treatment of various forms of spasticity with onabotulinumtoxin A in Germany. Prospective data were collected in an open multicenter patient registry from 2005 until 2010, encompassing the experience of ten specialized German centers in the treatment of spasticity using onabotulinumtoxin A in 508 patients with a total of 2005 treatment sessions. Disease entities comprised spasticity following stroke (both ischemic and hemorrhagic), traumatic brain injury, multiple sclerosis, cerebral palsy, and anoxia. Sustained improvement was observed in a variety of outcome parameters including goal attainment and motor performance scores for up to five repeated injection sessions. No significant differences between disease entities or between upper and lower limb treatment were observed with regard to efficacy and safety following onabotulinumtoxin A treatment. Minor to moderate side effects were reported in <1 % of the study population. We conclude that repetitive treatment of focal and multifocal spasticity with onabotulinumtoxin A provides a safe and efficacious therapeutic strategy for patients with different disease entities of the central nervous system.
EVALuna2:22323